Gleem - Carrasco, Freddy (Drawn & Quarterly, 2024)
A boy becomes bored at church with his grandmother until he tries a psychedelic drug. A group of friends are told that they need a rare battery if they want any chance of reviving their friend. Street style and cybernetics meet and burst into riotous dancing. Kindness and violence might not be as distant from each other as we think. GLEEM unsettles with a confidence that could make you believe in anything.